Respuesta :
Simplifying
3x + -18y = 4
Solving
3x + -18y = 4
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '18y' to each side of the equation.
3x + -18y + 18y = 4 + 18y
Combine like terms: -18y + 18y = 0
3x + 0 = 4 + 18y
3x = 4 + 18y
Divide each side by '3'.
x = 1.333333333 + 6y
Simplifying
x = 1.333333333 + 6y
3x + -18y = 4
Solving
3x + -18y = 4
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '18y' to each side of the equation.
3x + -18y + 18y = 4 + 18y
Combine like terms: -18y + 18y = 0
3x + 0 = 4 + 18y
3x = 4 + 18y
Divide each side by '3'.
x = 1.333333333 + 6y
Simplifying
x = 1.333333333 + 6y